2000
DOI: 10.3171/jns.2000.92.4.0646
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotection by the stable nitroxide Tempol during reperfusion in a rat model of transient focal ischemia

Abstract: Tempol provides significant neuroprotection after reperfusion in a rat model of transient focal ischemia. These results support the importance of ROS in reperfusion injury and encourage further study of this molecule as a therapeutic agent following thrombolysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
65
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 99 publications
(67 citation statements)
references
References 22 publications
2
65
0
Order By: Relevance
“…), and the carbonate radical (CO 3 .À ) (Augusto et al, 2008). Tempol readily crosses the BBB (Zhelev et al, 2009), and has previously been shown to provide neuroprotection as a free radical scavenger in several models of brain injury and ischemia (Kwon et al, 2003;Deng-Bryant et al, 2008;Rak et al, 2000;Cuzzocrea et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…), and the carbonate radical (CO 3 .À ) (Augusto et al, 2008). Tempol readily crosses the BBB (Zhelev et al, 2009), and has previously been shown to provide neuroprotection as a free radical scavenger in several models of brain injury and ischemia (Kwon et al, 2003;Deng-Bryant et al, 2008;Rak et al, 2000;Cuzzocrea et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Intraperitoneal administration of Tempol before and after reperfusion resulted in a significant decrease in IHC staining and a decrease in lipid peroxidation as demonstrated by a decrease in cerebral malondialdehyde levels. In another study, the middle cerebral artery of rats was occluded then Tempol was administered during the first 20 minutes of reperfusion [70]. Tempol treatment resulted in a significant, dose-dependent decrease in infarct size as measured by digital imaging of brain slices which were collected and fixed after four hours of reperfusion ( Figure 11).…”
Section: Ischemia-reperfusion Injury and Inflammationmentioning
confidence: 99%
“…According to this author the lower dose of tempol in this experiment could explain the reason why the effects were not impressive in this study. Scavenger activity of tempol was also described with use of lower doses than in this experiment (Rak et al 2000). Thus, more investigations would be needed to determine the appropriate dosage of tempol required in inducing protective effects in ischemia/reperfusion models.…”
Section: Discussionmentioning
confidence: 77%